2016
DOI: 10.1111/ajt.13794
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Inflammation With Ischemia: Implications for Donor Lung Preservation and Transplant Survival

Abstract: Lungs stored ahead of transplant surgery experience ischemia. Pulmonary ischemia differs from ischemia in the systemic organs in that stop of blood flow in the lung leads to loss of shear alone because the lung parenchyma does not rely on blood flow for its cellular oxygen requirements. Our earlier studies on the ischemia-induced mechanosignaling cascade showed that the pulmonary endothelium responds to stop of flow by production of reactive oxygen species (ROS). We hypothesized that ROS produced in this way l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…The major CAMs found on the surface of endothelial cells in injured tissue are the intercellular adhesion molecule (ICAM or CD54) and the vascular endothelial cell adhesion molecule (VCAM or CD106) [31,32] . We observed that the expression of CAMs that facilitate PMN-endothelial cell binding, are ischemia-ROS regulated ( Figure 2) [19,25] . Besides CAMs, there is hypoxiainducible factor 1α (HIF-1α), which transcriptionally regulates a host of inflammatory cytokines [33] .…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The major CAMs found on the surface of endothelial cells in injured tissue are the intercellular adhesion molecule (ICAM or CD54) and the vascular endothelial cell adhesion molecule (VCAM or CD106) [31,32] . We observed that the expression of CAMs that facilitate PMN-endothelial cell binding, are ischemia-ROS regulated ( Figure 2) [19,25] . Besides CAMs, there is hypoxiainducible factor 1α (HIF-1α), which transcriptionally regulates a host of inflammatory cytokines [33] .…”
Section: Introductionmentioning
confidence: 88%
“…We reported earlier that with loss of flow, the pulmonary endothelium in situ and endothelial cells in vitro(in flow chambers that mimic blood vessels) are activated via a KATP channel-NADPH oxidase 2 signaling pathway that causes the production of ROS (Figure 1) [18,21] . ROS production was evaluated from oxidation of various ROS-sensitive fluorescence dyes [dihydroethidine (DHE) for superoxide anion, dichlorofluorescein (DCF) for H2O2, and Amplex red (for intravascular H2O2)] [16,19,21] . ROS production that follows the ischemia signaling cascade that as we reported earlier, involves the "sensing" of the loss of flow stimulus by a complex machinery (for which we coined the term mechanosome) comprising of several elements namely caveolae and platelet endothelial cell adhesion molecule -1 (PECAM-1) [21] along with presumably other moieties like vascular endothelial growth factor receptor 2 (VEGFR-2) as reported by others [22] .…”
Section: New Strategies and Emerging Therapies For Lung Preservationmentioning
confidence: 99%
See 3 more Smart Citations